A comparative study of the photodissociation of physisorbed O-2 on Pt(111) and graphite - Siller, L; Bennett, S; Crabtree, H; Bennett, R; Wilkes, J; Lamont, C; MacDonald, M; Palmer, R; Foord, J (1997)
A comparative study of photodesorption from physisorbed oxygen layers on (highly oriented pyrolytic) graphite and Pt(111) surfaces has been carried out using continuously tuneable synchrotron radiation in the energy range 13-35 eV. The photodesorption of both O+ and O- species is detected. Through monitoring the ion yields as a function of the photon energy and coverage we have proposed a new mechanism for photodesorption of O- ions induced by inelastic scattering and attachment of photoelectrons originating from the adsorbate layer in the photon energy region between 25 and 30 eV.